2023
DOI: 10.1111/apa.16928
|View full text |Cite
|
Sign up to set email alerts
|

Major congenital heart defects are rarely diagnosed after newborns' hospital discharge with modern screening

I. Papunen,
T. Poutanen,
K. Ylänen

Abstract: AimOur aim was to assess undiagnosed congenital heart defects (CHD) after newborns' hospital discharge in patients with a murmur or CHD suspicion, to find out the signs that predict CHDs and to estimate the costs of the examinations.MethodsWe reviewed retrospective medical records of patients (n = 490) referred for the evaluation of CHD suspicion during 2017–2018.ResultsThe median age of the patients was 2.5 (IQR 0.5–7.4) years. Sixty‐three (13%) patients had an abnormal echocardiography. Neither ductal‐depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In Finland, most referrals due to murmurs or suspicion of CHD come from primary health care, so our algorithm could be most useful in screening for murmurs in that context 7 . The high prevalence of innocent murmurs detected in primary health care strains the limited resources of specialised care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland, most referrals due to murmurs or suspicion of CHD come from primary health care, so our algorithm could be most useful in screening for murmurs in that context 7 . The high prevalence of innocent murmurs detected in primary health care strains the limited resources of specialised care.…”
Section: Discussionmentioning
confidence: 99%
“…Although a murmur is the most common nding that raises suspicion of CHD, most of the children referred to paediatric cardiologists have an innocent murmur. According to some estimates, up to 90% of initial visits to paediatric cardiology clinics were due to an innocent murmur and thus unnecessary 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Meanwhile, Papinen et al report that only a few CHDs were confirmed after discharge in infants with suspected CHD when examined by foetal and newborn screening. 5 The authors point out that the high number of benign murmurs in children leads to numerous referrals and unnecessary healthcare costs.…”
Section: Clinicians Are Still Missing Critical Congenital Heart Defec...mentioning
confidence: 99%